2014
DOI: 10.1007/s12031-014-0241-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activities of Trichostatin A in U87 Glioblastoma Cells and Tumorsphere-Derived Cells

Abstract: Epigenetic alterations have been increasingly implicated in glioblastoma (GBM) pathogenesis, and epigenetic modulators including histone deacetylase inhibitors (HDACis) have been investigated as candidate therapies. GBMs are proposed to contain a subpopulation of glioblastoma stem cells (GSCs) that sustain tumor progression and therapeutic resistance and can form tumorspheres in culture. Here, we investigate the effects of the HDACi trichostatin A (TSA) in U87 GBM cultures and tumorsphere-derived cells. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…At present, the sorting methods of CSCs include flow cytometry based on special cell surface markers, the side population cell sorting technique, tumor sphere culturing and the ALDEFLUOR™ assay (6)(7)(8)(9). Previous studies have identified the CSCs from colon, breast and glioblastoma cancer, as well as other cancer cell lines, using the sphere culturing method (10)(11)(12). Tumor cell sphere culturing may be a convenient method for generating cancer stem-like cells to be used in the research of malignant behavior.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the sorting methods of CSCs include flow cytometry based on special cell surface markers, the side population cell sorting technique, tumor sphere culturing and the ALDEFLUOR™ assay (6)(7)(8)(9). Previous studies have identified the CSCs from colon, breast and glioblastoma cancer, as well as other cancer cell lines, using the sphere culturing method (10)(11)(12). Tumor cell sphere culturing may be a convenient method for generating cancer stem-like cells to be used in the research of malignant behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Research findings showed that TSA inhibits differentiation and proliferation and tumor sphere formation of glioblastoma (GBM) [ 52 , 141 , 142 ]. In addition, TSA upregulated the expression of numerous tumor suppressor genes through epigenetic modification in GBM [ 143 ].…”
Section: Anticancer Activity Of Tsamentioning
confidence: 99%
“…The TSA-induced cell cycle arrest in GBM was associated with the upregulation of p21 WAF1 and p53, and the downregulation of cell cycle regulators such as cdk4 and 6, and cyclin D1 with the reduction in phosphorylated Rb and Akt [ 141 , 142 , 144 , 145 ]. Sassi et al [ 52 ] reported that TSA inhibited the proliferation and colony formation of U87 glioblastoma cells without affecting their viability and migration. Similarly, Hoering et al [ 27 ] showed that TSA induces apoptosis of tumor cells, enhances the sensibility of GBM cells to innate immune responses in vitro and delays tumor growth of GBM xenografts in vivo .…”
Section: Anticancer Activity Of Tsamentioning
confidence: 99%
“…Many novel inhibitors of these key epigenetic regulatory enzymes have been developed and tested in clinical trials 2 . It has been demonstrated, that HDAC inhibitors sensitize gliomas and other types of cancer to chemotherapeutic agents and radiation, including: trichostatin (TSA), SAHA (vorinostat), valproic acid (VPA), LBH589 (panobinostat), MS275 (entinostat), PXD101 (belinostat) 319 . Studies in patient-derived glioblastoma cells demonstrated that SAHA, VPA, MS275, LBH589 and Scriptaid are effective radiosensitizers of gliomas 20 .…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of reports underscore the important roles of HDAC class IIa enzymes (HDAC4, 5, 7, 9) in GBM progression 3,2529 , invasion 3032 , responses to TMZ and radiotherapy 4,21,22 , and prognosis 33 . However, no studies have been reported to date on the efficacy of HDACs class IIa-selective inhibitors alone or in combination with TMZ and radiation therapy of GBM.…”
Section: Introductionmentioning
confidence: 99%